(untitled) (Journal of Scientific Research, 2020)
Three mononuclear copper(II) complexes of the type [Cu(bba)(bpy/phen/dpa)](ClO4)2 (1-3), where bba (N,N-bis(benzimidazol-2-ylmethyl)amine) and bpy (2,2’-bipyridine, 1) or phen (1,10-phenanthroline, 2) or dpa (2,2’-dipyridylamine, 3), have been isolated. The coordination geometry of 1 around copper(II) is square pyramidal. The electronic absorption (639-667 nm) and EPR spectral parameters (g||, 2.25; A||, 181-186 × 10-4 cm-1; g||/A||, 122−134 cm) reveal that 1-3 possesses a square pyramidal geometry with CuN5 chromophore. Different spectral and electrochemical measurements clearly demonstrate partial intercalative interaction of 1-3 to CT DNA. Complexes strongly quench the intrinsic fluorescence of BSA through a static quenching procedure by forming BSA-(1/2/3) adducts, which are stabilized by hydrophobic interactions. The number of binding sites and binding constants were calculated. The energy transfer from BSA to Cu(II) complexes occurs with high probability. Notably, 1-3 exhibit more effective pUC 19 DNA cleavage in the presence of H2O2. Complexes 2 and 1 show remarkable cytotoxicity (IC50: 2, 2.17; 1, 8.33 mM) against human cervical carcinoma cells (HeLa) and more potent than cisplatin (IC50, 16.40 mM) while 3 exhibits less cytotoxicity (IC50, 20.82 mM). The DNA binding propensity, cleavage ability and cytotoxicity follow the order 2>1>3. Interestingly, they are non-toxic to healthy cells.